Squeezing More Juice out of Dielectric Elastomer Generators - Rosset , Samuel; Anderson , Iain A. (Frontiers in Robotics and AI, 2022)
Dielectric elastomer generators are soft structures capable of converting mechanical energy into electrical energy. Here, we develop a theoretical model of the triangular harvesting cycle that enables the harvesting of most of the available electrical energy while not requiring active monitoring of the charge-voltage state on the DEG. This cycle is therefore interesting for small-scale generators for which a monitoring circuit would be energetically too costly. Our model enables the identification of the optimal value of the circuit's parameters such as storage capacitor and priming voltage values and show that for capacitance swings up to 6, 94% of the available electrical energy can be harvested. The model is experimentally validated with a conical generator, and the effect of non-constant deformation amplitudes is examined. Energy densities up to 46 mJ/cm^3 were obtained for an electric field of 50 V/um.